2021
DOI: 10.1177/26323524211032984
|View full text |Cite
|
Sign up to set email alerts
|

New public health approaches to palliative care, a brave new horizon or an impractical ideal? An Integrative literature review with thematic synthesis

Abstract: Access to palliative care for marginalized communities is frequently problematized as a major challenge facing palliative care services. The traditional response of asking what services can do for the disadvantaged has been invigorated by a new wave of public health measures that embrace death and dying as social processes and ask, what can be done together with such communities as partners working in palliative care. Such work has generated a significant amount of academic, social and political interests over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 131 publications
1
11
0
Order By: Relevance
“…This review concluded that strong leadership is critical to helping address these tensions. 35 In this study, organizations that had a successful Nav-CARE implementation were already well connected to their community having built a strong network of relationships. 39 that clearly outline the role and required preparation.…”
Section: Scaling Deep: Influencing Relationships and Valuementioning
confidence: 89%
“…This review concluded that strong leadership is critical to helping address these tensions. 35 In this study, organizations that had a successful Nav-CARE implementation were already well connected to their community having built a strong network of relationships. 39 that clearly outline the role and required preparation.…”
Section: Scaling Deep: Influencing Relationships and Valuementioning
confidence: 89%
“…[ 8 ] The public health approach to palliative care is premised on the principle of community engagement, in which people in society own the responsibility of caring for each other. [ 18 ] This approach empowers people in the community to support patients and families facing the end of life by responding to the needs and wishes of the dying patients and their families, creating leaders from within the community for sustainability, developing collaborations with community groups and stakeholders, and working in alignment with healthcare professionals. [ 12 , 18 - 20 ]…”
Section: Seeing Primary Palliative Care Through the Lens Of Public He...mentioning
confidence: 99%
“…A health promotion approach to palliative care is gaining traction internationally in response to issues related to aging populations and a professionalization of end-of-life (EoL) care. 1 3 Based on the notion that the EoL primarily is a social issue that concerns everyone, health promotion approaches to palliative care often work with communities to increase engagement in EoL issues to enhance a sense of control and support for those who are dying, grieving, or are providing care. 2 , 4 6 Although the relevance of these initiatives is increasingly recognized, researchers in this field have pointed to the lack of evaluations of the impact of this approach.…”
Section: Introductionmentioning
confidence: 99%
“… 1 3 Based on the notion that the EoL primarily is a social issue that concerns everyone, health promotion approaches to palliative care often work with communities to increase engagement in EoL issues to enhance a sense of control and support for those who are dying, grieving, or are providing care. 2 , 4 6 Although the relevance of these initiatives is increasingly recognized, researchers in this field have pointed to the lack of evaluations of the impact of this approach. 3 , 7 , 8 Furthermore, evaluations of community-based initiatives are particularly lacking.…”
Section: Introductionmentioning
confidence: 99%